Transactions on Pattern Languages of Programming II Special Issue on Applying Patterns - Noble, James; Johnson, Ralph; Avgeriou, Paris; Harrison, Neil B.; Zdun, Uwe.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The Transactions on Pattern Languages of Programming subline aims to publish papers on patterns and pattern languages as applied to software design, development, and use, throughout all phases of the software life cycle, from requirements and design to implementation, maintenance and evolution. The primary focus of this LNCS Transactions subline is on patterns, pattern collections, and pattern languages themselves. The journal also includes reviews, survey articles, criticisms of patterns and pattern languages, as well as other research on patterns and pattern languages. This book, the second volume in the Transactions on Pattern Languages of Programming series, presents five papers that have been through a careful peer review process involving both pattern experts and domain experts. The papers demonstrate techniques for applying patterns in an industrial or research setting. Some have confronted the topic within software engineering; others offer approaches in other pattern domains, which is an indication of the diverse fields where patterns are applied.
Keywords: Computer science; Computer network architectures; Software engineering; Information Systems; Computer Science; Software Engineering/Programming and Operating Systems; Programming Techniques; Programming Languages, Compilers, Interpreters; Computer Systems Organization and Communication Networks; Management of Computing and Information Systems